Broad-spectrum antivirals against viral fusion - Vigant, Frederic (Nat Rev Microbiol, 2015)
Effective antivirals have been developed against specific viruses, such as HIV, Hepatitis C virus and influenza virus. This 'one bug–one drug' approach to antiviral drug development can be successful, but it may be inadequate for responding to an increasing diversity of viruses that cause significant diseases in humans. The majority of viral pathogens that cause emerging and re-emerging infectious diseases are membrane-enveloped viruses, which require the fusion of viral and cell membranes for virus entry. Therefore, antivirals that target the membrane fusion process represent new paradigms for broad-spectrum antiviral discovery. In this Review, we discuss the mechanisms responsible for the fusion between virus and cell membranes and explore how broad-spectrum antivirals target this process to prevent virus entry. SUPPLEMENTARY INFORMATION: The online version of this article (doi:10.1038/nrmicro3475) contains supplementary material, which is available to authorized users.